Long-term Effectiveness of Online Anaphylaxis Education for Pharmacists - Salter, Sandra M (American Journal of Pharmaceutical Education, 2014)
Objective. To evaluate the long-term effectiveness of an Australasian Society of Clinical Immunology and Allergy (ASCIA) anaphylaxis e-learning program compared to lectures or no training. Design. A controlled interrupted-time-series study of Australian pharmacists and pharmacy students who completed ASCIA anaphylaxis e-learning or lecture programs was conducted during 2011-2013. Effectiveness was measured using a validated test administered pretraining, posttraining, and 3 and 7 months after training. Assessment. All learning groups performed significantly better on all posttests compared to the pretest, and compared to a control group (p<0.001). The proportion of e-learners achieving the minimum standard for anaphylaxis knowledge improved from 45% at pretest to 87% at 7 months. Conclusion. The ASCIA e-learning program significantly increased anaphylaxis knowledge. The high proportion of participants achieving the minimum standard at 7 months indicates long-term knowledge change.